Ultrasonically actuated neural probes for reduced trauma and inflammation in mouse brain - Po-Cheng Chen; Catharine G. Young; Chris B. Schaffer; Amit Lal (Microsystems & Nanoengineering, 2022)
Abstract Electrical neural recordings measured using direct electrical interfaces with neural tissue suffer from a short lifespan because the signal strength decreases over time. The inflammatory response to the inserted microprobe can create insulating tissue over the electrical interfaces, reducing the recorded signal below noise levels. One of the factors contributing to this inflammatory response is the tissue damage caused during probe insertion. Here, we explore the use of ultrasonic actuation of the neural probe during insertion to minimize tissue damage in mice. Silicon neural microprobes were designed and fabricated with integrated electrical recording sites and piezoelectric transducers. The microprobes were actuated at ultrasonic frequencies using integrated piezoelectric transducers. The microprobes were inserted into mouse brains under a glass window over the brain surface to image the tissue surrounding the probe using two-photon microscopy. The mechanical force required to penetrate the tissue was reduced by a factor of 2–3 when the microprobe was driven at ultrasonic frequencies. Tissue histology at the probe insertion site showed a reduced area of damage and decreased microglia counts with increasing ultrasonic actuation of the probes. Two-photon imaging of the microprobe over weeks demonstrated stabilization of the inflammatory response. Recording of electrical signals from neurons over time suggests that microprobes inserted using ultrasound have a higher signal-to-noise ratio over an extended time period.